2019
DOI: 10.3892/ol.2019.10694
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑23a inhibits endometrial cancer cell development by targeting SIX1

Abstract: The present study focused on exploring the inhibitory mechanism of microRNA (miR)-23a in endometrial cancer. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) was used to investigate miR-23a expression in endometrial tissues and endometrial cancer cells. A colony formation assay using crystal violet staining was performed to compare cell proliferation, while wound-healing and Transwell assays were performed to compare cell migration and invasion. Subsequently, bioinformatics and a lucifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…Similarly, miR-574-5p was dysregulated in the mediastinal lymph node in pigs infected with porcine circovirus type 2 and was predicted to be involved in the regulation of the T cell receptor signaling pathway [ 79 ]. Related to reproductive processes, a dysregulation in miR-23a and miR-574 family members has been related to pathological pregnancy [ 80 , 81 ] and endometrial cancer in humans [ 82 ]. Therefore, the literature indicates that these two miRNAs play a key role in immune and reproductive processes, suggesting that they could also be involved in the modulation of the female immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-574-5p was dysregulated in the mediastinal lymph node in pigs infected with porcine circovirus type 2 and was predicted to be involved in the regulation of the T cell receptor signaling pathway [ 79 ]. Related to reproductive processes, a dysregulation in miR-23a and miR-574 family members has been related to pathological pregnancy [ 80 , 81 ] and endometrial cancer in humans [ 82 ]. Therefore, the literature indicates that these two miRNAs play a key role in immune and reproductive processes, suggesting that they could also be involved in the modulation of the female immune response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in NSCLC, miR-133a inhibits cell proliferation with poor prognosis by targeting YES1 [16]. miR-23a was downregulated in endometrial cancer, which inhibited the development of endometrial cancer by targeting SIX1 [17]. In contrast, in gastric cancer, miR-23a was upregulated with the promoting role in gastric cancer through targeting SPRY2 [18].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs exert their functions by binding to the target genes at a post-transcriptional level (33,34). Previous evidence has suggested that miR-448 exhibits differing functions in human diseases.…”
Section: Discussionmentioning
confidence: 99%